Analisis Daya Saing Usahatani Rumput Laut Di Kabupaten Konawe Selatan - Yusriadin Yusriadin; Budiyanto Budiyanto; Rosmawaty Rosmawaty; Ine Fausayana (Jurnal Sosio Agribisnis, 2019)
The research aims to know the competitiveness of seaweed farming in south Konawe regency. The population of this research is all of seaweed farmers in south Konawe which account for 498 farmers; while, the number of samples is 221 farmers. Samples were selected by Cluster Random Sampling method which then chosen randomly by means of Simple Random Sampling method. Type and data source used is primary and secondary data. The data was technically collected by direct interview with respondents and study literature. The variable comprises of respondent’s identity (age, education level, number of family dependents, and farming experience) and Competitiveness of seaweed farming (revenue, input tradable cost,input non tradable cost, private prices and sosial prices). The data analysis is the Policy Analysis Matrix. Competitively and comparatively, seaweed farming in south Konawe regency is relatively competitive. This can be seen from the value of Privat Cost Rasio namely 0,34 and the value of Domestic Resources Cost Ratio which is 0,26 or less than one.Keywords: Competitiveness; Farming; Seaweed